2016
DOI: 10.1002/cam4.714
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of survival of diffuse large B‐cell lymphoma patients via the expression of three inflammatory genes

Abstract: Currently, several gene‐expression signatures that were used to predict survival of diffuse large B‐cell lymphoma (DLBCL) patients, showed a restriction on the practical work for lack of convenient operation. In this study, we screened inflammatory genes whose expression correlated with survival of DLBCL and established a predictive model including IL6, IL1A and CSF3 through multivariate Cox regression based on the expression of these three genes. We validated the model at protein level in our clinical serum c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Li et al [ 10 ] reported that the inflammation-related gene IL-1β promotes stemness and invasiveness of colon tumor through activation of CSC self-renewal and EMT. Zhao et al [ 11 ] reported that a three inflammatory gene model including IL-6 , IL-1A and CSF3 could predict survival of diffuse large B-cell lymphoma patients, and patients with high-risk score of this signature had significantly shorter survival than those with low-risk score. The pathway analysis comprised of IRGs could determine genetic risk factors for cancers that might have an underappreciated modest inflammatory component.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [ 10 ] reported that the inflammation-related gene IL-1β promotes stemness and invasiveness of colon tumor through activation of CSC self-renewal and EMT. Zhao et al [ 11 ] reported that a three inflammatory gene model including IL-6 , IL-1A and CSF3 could predict survival of diffuse large B-cell lymphoma patients, and patients with high-risk score of this signature had significantly shorter survival than those with low-risk score. The pathway analysis comprised of IRGs could determine genetic risk factors for cancers that might have an underappreciated modest inflammatory component.…”
Section: Introductionmentioning
confidence: 99%
“…Anemia reflects an unfavorable prognosis of tumor course [11,12]. According to the literature data, blood cytokine levels are important for predicting the survival of patients with hematological neoplasms, in particular, those with NHL [3,4]. This is due to the influence of cytokines on the proliferation, differentiation, and migration of tumor and stromal cells, as well as on the regulation of communication between a tumor and its stroma, and the interaction of a tumor with its extracellular matrix [15].…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the relationship between levels of cytokines and survival is studied, as a rule, in patients with concrete mature lymphoid neoplasms, such as diffuse large B-cell lymphoma [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Functionally, PCDH7 silence inhibited ERK activation and tumor growths [ 14 ]. Zhao and his group observed that three inflammatory genes (CSF3, IL-1A, and IL-6) were associated with long-term survivals of patients with B-cell lymphoma [ 15 ]. To date, there are no researches regarding a prevailing model based on inflammation-related genes for the prediction of clinical survivals of LUAD patients.…”
Section: Introductionmentioning
confidence: 99%